An investigation into the constraints to the development and mainten ance of an appropriate rural feeder (District road network in Uganda - Seguya, Frederick Ronald (Kampala, 2001)
Thesis (M.Sc., Civil Eng.) - Makerere University, 2001
Includes bibliographical references (p.78-87)
Keywords: Rural roads